Enhancing supply chain resilience through supply chain finance: Moderating role of supply chain disruption - Aamir Shahzad; Muhammad Irfan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Developing countries face economic disruptions due to financing limitations generated by traditional financing practices. Although supply chain finance (SCF) is recognized as a significant financing strategy in academic literature, it is still overlooked as a proactive financial strategy to mitigate disruptions. Recent research has examined SCF as a strategic approach, and how it mitigates disruptions caused by funding system deficiencies, ultimately enhancing supply chain resilience SCR. We extensively reviewed the current literature and tested hypotheses using partial least squares structural equation modeling (PLS-SEM) with survey data collected from manufacturing firms in Pakistan. Our study findings indicate that the adoption of SCF is primarily influenced by three factors: collaboration, the role of financial institutes, and digitalization. Furthermore, our research offers empirical evidence supporting the use of SCF to enhance SCR. Moreover, we validate that the role of supply chain disruption SCD is negative but significant in the relationship between SCF and SCR. This paper fills a gap in the current stream of literature by empirically investigating the impact of SCF on achieving SCR. The novelty of this study lies in integrating the antecedents and consequences of SCF adoption into a single framework.
Keywords: 330; Supply chain finance; supply chain resilience; supply chain disruption; digitization